2017
DOI: 10.1016/j.jcrc.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric intermediate care and pediatric intensive care units: PICU metrics and an analysis of patients that use both

Abstract: Purpose To examine how intermediate care units (IMCUs) are used in relation to pediatric intensive care units (PICUs), characterize PICU patients that utilize IMCUs, and estimate the impact of IMCUs on PICU metrics. Materials & Methods Retrospective study of PICU patients discharged from 108 hospitals from 2009–2011. Patients admitted from or discharged to IMCUs were characterized. We explored the relationships between having an IMCU and several PICU metrics: physical length-of-stay (LOS), medical LOS, disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
(21 reference statements)
2
15
0
Order By: Relevance
“…Moreover, a separate analysis has demonstrated that some of the differences observed in subgroups may represent chance variation 5 . Third, the Pediatric Airway Management Project trial reported a higher ICU mortality rate than most pediatric ICUs currently report; however, 75% of the patients in the trial were in cardiac arrest prior to ICU admission, and the overall survival rates of these patients were similar to those reported in recently published trials of therapeutic hypothermia in this population 24–27 . Our study suggests that the apparent gain in sensitivity with the proposed ICU‐free days outcome measure might be limited to pediatric populations with high mortality.…”
Section: Limitationssupporting
confidence: 77%
“…Moreover, a separate analysis has demonstrated that some of the differences observed in subgroups may represent chance variation 5 . Third, the Pediatric Airway Management Project trial reported a higher ICU mortality rate than most pediatric ICUs currently report; however, 75% of the patients in the trial were in cardiac arrest prior to ICU admission, and the overall survival rates of these patients were similar to those reported in recently published trials of therapeutic hypothermia in this population 24–27 . Our study suggests that the apparent gain in sensitivity with the proposed ICU‐free days outcome measure might be limited to pediatric populations with high mortality.…”
Section: Limitationssupporting
confidence: 77%
“…While some studies have suggested improved efficiency of care through utilization of IMCUs, others have shown that standard ICU markers of quality are not improved. [33][34][35] Due to this controversy, as well as a variable return on investment, IMCUs are not feasible in all hospital settings. Furthermore, similar to the PICU, the potential exists to over-utilize this level of care with the same resultant risk of lack of bed availability during times of need.…”
Section: Discussionmentioning
confidence: 99%
“…19(p10) Previous research found no association between having an intermediate care, or step-down, unit and most measures of PICU efficiency (eg, length of stay, readmissions). 20 However, little has been reported on the overall experiences of PICU health care providers or families working in such a unit. We found support for a distinct space with proximity to a traditional PICU focusing on the care required by PCCPs.…”
Section: Theme 2: Designation Of a Primary Intensivistmentioning
confidence: 99%